Numerical simulation of condensation in microchannels between spherical particles. (November 2016) - Liu, Dongren; Peng, Hao; Ling, Xiang; Wang, Yan; Zhou, Lingjun
In this article, a numerical investigation of vapor condensation in a two-dimensional ordered microchannel was conducted with computational fluid dynamics software Fluent. A simplified physical model was built up to simulate a rectangular channel filled with particles. A constant wall heat flux was added to the side walls of the rectangular channel. Volume of fluid model was adopted to pursue the interface of the gas and liquid. The results showed that a better heat transfer performance could be obtained with the porous structure. The local heat transfer coefficient obtained from simulation was in good accordance with the former experimental data, which increased with the increase in fluid velocity and decreased along the flow direction. Parametric analyses were conducted concerning the effects of initial vapor velocity u 0, initial temperature T 0, and wall heat flux qw on local heat transfer coefficient. The velocity u 0 played a significant role during the process of condensation. Temperature distributions along the porous channel and side walls were also analyzed. The results showed that the temperature decreased along the flow direction and increased with the increase in fluid velocity.